Strain related infectivity of Neisseria gonorrhoeae for the guinea-pig subcutaneous chamber and the variability of the immune resistance in different breeds of guinea-pig. Issue 2 (April 1978) - Novotny, P; Broughton, E S; Cownley, K; Hughes, M; Turner, W H
Abstract : The ability of gonococci to infect the subcutaneous chamber in guinea-pigs is strictly strain related. This ability was usually present in prototrophic strains and auxotrophs requiring proline only which were obtained from patients with uncomplicated gonorrhoea, but it was invariably absent in Neisseria gonorrhoeae auxotypes requiring arginine, uracil, and hypoxanthine, or arginine only for growth. All the strains obtained from disseminated gonococcal infections (all dependent upon arginine, uracil, and hypoxanthine) were unable to infect the guinea-pig chamber. Hence, the high invasiveness of N. gonorrhoeae for man and its infectivity for guinea-pig chambers appear to be unrelated properties. Although guinea-pigs of the same origin (Dunkin-Hartley) were used throughout, the degree of immune resistance was found to differ between the lines supplied by various breeders–that is, after a standard immunisation schedule using whole cell gonococcal vaccines, the homologous immune resistance to challenge varied from weak or non-existent in some lines, to highly resistant in others.